Regional variation of extended-spectrum beta-lactamase (ESBL)-producing enterobacterales, fluoroquinolone-resistant salmonella enterica and methicillin-resistant staphylococcus aureus among febrile patients in sub-saharan Africa - Moirongo, Rehema Moraa; Lorenz, Eva; Ntinginya, Nyanda E.; Dekker, Denise Myriam; Fernandes, Jose; Held, Jana; Lamshoeft, Maike; Schaumburg, Frieder; Mangu, Chacha; Sudi, Lwitiho; Sié, Ali; Souares-Coutant, Aurélia; et al. (Frontiers in microbiology, 2020)
Background Antimicrobial resistance (AMR) thwarts the curative power of drugs and is a present-time global problem. We present data on antimicrobial susceptibility and resistance determinants of bacteria the WHO has highlighted as being key antimicrobial resistance concerns in Africa, to strengthen knowledge of AMR patterns in the region. Methods Blood, stool, and urine specimens of febrile patients, aged between >= 30 days and <= 15 years and hospitalized in Burkina Faso, Gabon, Ghana, and Tanzania were cultured from November 2013 to March 2017 (Patients > 15 years were included in Tanzania). Antimicrobial susceptibility testing was performed for all Enterobacterales andStaphylococcus aureusisolates using disk diffusion method. Extended-spectrum beta-lactamase (ESBL) production was confirmed by double-disk diffusion test and the detection ofbla(CTX-M),bla(TEM)andbla(SHV). Multilocus sequence typing was conducted for ESBL-producingEscherichia coliandKlebsiella pneumoniae, ciprofloxacin-resistantSalmonella entericaandS. aureus. Ciprofloxacin-resistantSalmonella entericawere screened for plasmid-mediated resistance genes and mutations ingyrA, gyrB, parC, and parE.S. aureusisolates were tested for the presence ofmecAand Panton-Valentine Leukocidin(PVL)and further genotyped byspatyping. Results Among 4,052 specimens from 3,012 patients, 219 cultures were positive of which 88.1% (n= 193) were Enterobacterales and 7.3% (n= 16)S. aureus. The prevalence of ESBL-producing Enterobacterales (all CTX-M15 genotype) was 45.2% (14/31; 95% CI: 27.3, 64.0) in Burkina Faso, 25.8% (8/31; 95% CI: 11.9, 44.6) in Gabon, 15.1% (18/119; 95% CI: 9.2, 22.8) in Ghana and 0.0% (0/12; 95% CI: 0.0, 26.5) in Tanzania. ESBL positive non-typhoidSalmonella(n= 3) were detected in Burkina Faso only and methicillin-resistantS. aureus(n= 2) were detected in Ghana only. While sequence type (ST)131 predominated among ESBLE. coli(39.1%;9/23), STs among ESBLK. pneumoniaewere highly heterogenous. Ciprofloxacin resistant ntSalmonellawere commonest in Burkina Faso (50.0%; 6/12) and all harboredqnrBgenes.PVLwere found in 81.3%S. aureus. Conclusion Our findings reveal a distinct susceptibility pattern across the various study regions in Africa, with notably high rates of ESBL-producing Enterobacterales and ciprofloxacin-resistant ntSalmonellain Burkina Faso. This highlights the need for local AMR surveillance and reporting of resistances to support appropriate action.
Gesehen am 14.12.2020